Analisis Hubungan Unsur Cuaca Terhadap Fluktuasi Produksi Sawit di Kab. Konawe Utara: Relationship Analysis of Weather Elements Toward Palm Production Fluctuation in North Konawe Regency - Musyadik - - (Jurnal Ecosolum, 2020)
Oil palm (Elaeis guineensis Jacq) is one of the important commodities in Indonesia and has bright prospects for development. The increase in demand for palm oil per year continues to increase, this is evidenced by the increase in CPO production from 2011 to 2015 increased by around 5.38 to 8.42 percent per year. The increase in oil palm production is allegedly related to weather effects such as rainfall in a certain period. This research is indispensable as a basis for predicting and evaluating the production and fresh fruit of oil palm in relation to climate elements. The dependent variable data used in this study were primary data on the production of fresh fruit bunches for oil palm PTPN Wilayah XIV as Asera plantation unit. While the independent variable data used are air temperature, rainfall, and solar radiation (2013-2015) which are analyzed using the correlation test by analyzing the degree or closeness of the relationship between climatic factors including air temperature, rainfall, and solar radiation with oil palm production in North Konawe Regency and knowing the form of the relationship between the two variables using a scatter diagram. The results of the analysis show that temperature and oil palm production have a very strong positive relationship with a correlation coefficient of 1.0. Rainfall and oil palm production have a moderate positive relationship with a correlation coefficient of 0.6, solar radiation and oil palm production in North Konawe have no relationship during 2013-2015, but solar radiation is closely related to rainfall and temperature variables.